2010
DOI: 10.1139/x09-202
|View full text |Cite
|
Sign up to set email alerts
|

Effects of experimental freezing on soil nitrogen dynamics in soils from a net nitrification gradient in a nitrogen-saturated hardwood forest ecosystem

Abstract: This study examined effects of soil freezing on N dynamics in soil along an N processing gradient within a mixed hardwood dominated watershed at Fernow Experimental Forest, West Virginia. Sites were designated as LN (low rates of N processing), ML (moderately low), MH (moderately high), and HN (high). Soils underwent three 7-day freezing treatments (0, -20, or -80 8C) in the laboratory. Responses varied between temperature treatments and along the gradient. Initial effects differed among freezing treatments f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 46 publications
(68 reference statements)
2
12
0
Order By: Relevance
“…It is possible that increases in nitrification following soil frost may also contribute to NO 3 − leaching (Gilliam et al ., ). In our study, the low concentrations of NH 4 + and high concentrations of NO 3 − in the B horizon of the snow‐removal plots suggest that most of the excess NH 4 + in the Oa horizon was nitrified.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is possible that increases in nitrification following soil frost may also contribute to NO 3 − leaching (Gilliam et al ., ). In our study, the low concentrations of NH 4 + and high concentrations of NO 3 − in the B horizon of the snow‐removal plots suggest that most of the excess NH 4 + in the Oa horizon was nitrified.…”
Section: Discussionmentioning
confidence: 97%
“…Increases in N export following experimental soil freezing in mixed hardwood forests at the Fernow Experimental Forest, West Virginia were attributed in part to elevated rates of nitrification (Gilliam et al ., ), but elevated N leaching could not be explained by increased rates of nitrification alone in the majority of other forests studied (Fitzhugh et al ., ; Callesen et al ., ; Christopher et al ., ; Hentschel et al ., ). Rather, most studies purport that reduced plant uptake is the primary mechanism for increased N losses (Boutin & Robitaille, ; Fitzhugh et al ., ; Groffman et al ., ; Matzner & Borken, ; Kreyling, ; Brooks et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…, 2010). Gilliam et al. (2010) suggested that mild freezing may inhibit N mineralizing microbes and stimulate N immobilizing groups.…”
Section: Discussionmentioning
confidence: 99%
“…Seasonal patterns of NH 4 + and NO 3 – may be attributed to freezing, which can disrupt coupling between soil N mineralization and microbial immobilization of N (Maithani et al. , 1998; Gilliam et al. , 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Increased frequency and duration of soil frost has been associated with changes in microbial activity (Gilliam et al 2010), injury of fine roots (Tierney et al 2001;Cleavitt et al 2008), and increased export of carbon and nutrients, such as nitrogen during the growing season, which is associated with changes in microbial activity (Matzner and Borken 2008). Kreyling et al (2012) examined the effects of a range of freeze-thaw scenarios and their effects on root injury and fungal community composition, biomass, and root injury.…”
Section: Potential Effect Of Climate Change On Microbial Interactionsmentioning
confidence: 99%